Arrival and departure patterns of Eurasian Curlew Numenius a. arquata wintering on the River Severn estuary, Gloucestershire, southwest England - Sanders, John D.; Rees, Eileen C. (Wildfowl, 2018)
Regular spring and autumn observations of colour-ringed Eurasian Curlew Numenius a. arquata wintering on the River Severn estuary in Gloucestershire, UK, marked during 2010–2013 inclusive, were used to locate surviving ringed individuals (n = 147 birds resighted) and describe the timing of their annual arrivals and departures. Breeding locations reported for 18 birds were from Fennoscandia (5), the Netherlands or Germany (6) and Britain (7). Fennoscandian birds remained significantly later on the estuary each year than the 13 individuals known to breed in Britain, the Netherlands or Germany. Departure dates recorded for 109 Curlew during a more intensive survey in 2016 similarly found that onset of spring migration was significantly later for birds known (or thought because they remained on the estuary until April) to be of Fennoscandian origin. Curlew returned from breeding grounds to the Severn estuary from the first week of June onwards, sooner than reported in previous studies, but with limited evidence for differences in return dates for Curlew breeding in different parts of Europe. Whether early arrival is associated with a failed breeding attempt could not be determined.